mCHW : a mobile learning intervention for community health workers - Winters, N; Oliver, M; Mukami, D; Lakati, A; Mbae, S; Wanjiru, H; Geniets, A; Henry, J; Langer, L; Hakimi, L; Robson, J; Rega, I; et al. (University of Oxford, 2015)
The mCHW project (http://www.mchw.org) – a mobile learning intervention for community health workers (CHWs) – represents an ongoing research collaboration between the Institute of Education, University of London (IoE), the University of Oxford and Amref Health Africa to advance the training and supervision of community health volunteers in Kenya, seeking improved access to primary health care for the marginalised communities of Makueni County and the Kibera informal settlement.